Challenges and opportunities for the re-use of New Data Types (NDTs) in a changing landscape - Kondyli, Dimitra; Klironomos , Nicolas (The Greek Review of Social Research, 2024)
Over the past fifteen years, technology has contributed to the emergence of new types of data, particularly big data, influencing the methods of observation, study, and measurement of social phenomena from the perspective of the social sciences. The increasing digitization of social activities generates vast amounts of data that fuel contemplation about the way modern societies function. Additionally, factors such as the recent COVID-19 pandemic with mandatory social distancing have contributed to the creation of a favourable environment for the generation of new types of data, with an emphasis on big data. Within this ongoing transformation of the data landscape, we will attempt to pose questions related to the environment of Data Repositories/Research Infrastructures and the means/methods of addressing and managing these data. It appears that social research is shifting towards a more "data-driven approach", which requires new skills and capabilities at the intersection of the computational and social sciences. One of the major issues that arise is the potential for collaborations between data organizations and researchers/users of data to promote not only a culture of data sharing but also the reuse of such data. This work will be based on primary and secondary sources generated within the framework of research projects in collaboration with CESSDA ERIC (European Social Science Data Archives-European Research Infrastructures), as well as literature on the management of data from various sources, with an emphasis on their legal/ethical and technical aspects.